What Drives Consumers to Use Syariah M-Banking to Purchase E-Money? Integration of UTAUT 2 and Mobile Service Quality - Septiani, Alfian Nisa; Berakon, Izra; Pertiwi, Ruspita Rani; Pradana, Mahatva Yoga Adi; Kamal, Safwan (Universitas Islam Internasional Indonesia, 2022)
This study investigates what factors persuade consumers to purchase e-money via syariah m-banking applications. Researchers extended the Unified Theory of Acceptance and Use of Technology (UTAUT 2) to find new information as well as to accommodate the limitations and discussions of previous studies. A purposive sampling technique was adapted to select respondent criteria. The collected data from 120 respondents were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM), supported by WarpPLS 8.0, through three main stages of analysis: measurement model, structural model, and hypothesis testing. Additional analysis was undertaken to produce robust findings by explaining multicollinearity, common method bias, and multigroup analysis by categorizing two groups of respondents (male and female). Researchers found that only social influence and hedonic motivation have a significant effect on trust from the UTAUT 2 model. On the other hand, two exogenous constructs in the mobile service quality model proved to have a significant effect on trust, security (privacy), and practicality. Furthermore, the research showed that trust is a fundamental factor in influencing continuance intention because it produces the largest effect size (f-square) and significant path coefficient value. The findings should encourage all Islamic banking stakeholders and practitioners to increase individual trust by creating educational and innovative programs connected with consuming digital banking services, especially e-money purchases.